ANALISIS DIGITALISASI KEUANGAN TERHADAP EFESIENSI PRODUKTIVITAS USAHA KECIL DAN MENENGAH (UMKM) - Poddala, Paramita; Poddala, Anggi; Farild, Miftha (Assets: Jurnal Ekonomi, Manajemen, dan Akuntansi, 2025)
The purpose of this study is to examine how financial digitization helps micro, small, and medium enterprises (MSMEs) in the digital economy era improve their productivity and efficiency. This study focuses on MSMEs in Makassar City. The research subjects are 10 MSME players who have used at least one form of digital financial application. A descriptive qualitative method was used, involving observation, documentation, and in-depth interviews with MSME operators from various industries. The results of the study indicate that the use of digital financial applications and the QRIS payment system has helped MSME operators record transactions more quickly, create more accurate financial reports, and facilitate data-driven decision-making processes. Thus, digitalization has a significant impact on improving the efficiency and productivity of small and medium-sized enterprises (SMEs) in Makassar City. Digital transformation, particularly in the form of utilizing digital financial technology, e-commerce platforms, and financial recording and online marketing applications, has helped daily operations, financial management, and market growth for local small and medium-sized enterprises (SMEs).